2022
DOI: 10.1097/gox.0000000000004083
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Biologic Mesh Reduces Postoperative Complications Compared to Biologic Mesh after Ventral Hernia Repair

Abstract: Background: The use of biologic mesh to reinforce the abdominal wall in ventral hernia repair has been proposed as a viable alternative to synthetic mesh, particularly for high-risk patients and in contaminated settings. However, a comparison of clinical outcomes between the currently available biologic mesh types has yet to be performed. Methods: We performed a retrospective analysis of 141 patients who had undergone ventral hernia repair with biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…We found no difference in recurrence rates based on mesh location, which is consistent with recent studies . Furthermore, high-quality data are scarce regarding the superiority of any specific mesh type . In our study, we found that biologic mesh and resorbable synthetic mesh were associated with an increase in risk of recurrence compared to permanent synthetic mesh.…”
Section: Discussionmentioning
confidence: 99%
“…We found no difference in recurrence rates based on mesh location, which is consistent with recent studies . Furthermore, high-quality data are scarce regarding the superiority of any specific mesh type . In our study, we found that biologic mesh and resorbable synthetic mesh were associated with an increase in risk of recurrence compared to permanent synthetic mesh.…”
Section: Discussionmentioning
confidence: 99%
“…Тем не менее большое число авторов сходятся во мнении, что использование биологических сеток гарантированно приводит к более высокому проценту осложнений в послеоперационном периоде [37]. Авторы указывают образование сером, нагноение парапротезной области, инфекционные осложнения со стороны раны, рецидивы грыж [38,39] [42].…”
Section: обзор литературыunclassified
“…10,14 The most popular biologic mesh substrates include human, bovine, or porcine tissues, where various processing techniques preserve different cellular and extracellular materials to encourage host cell integration. 15 Synthetic meshes are generally made of manufactured polymers, such as polypropylene, polyester, or expanded polytetrafluorethylene, which may be combined with other materials to make composite matrices with varied physical properties. 14 These synthetic sheets of material can be knitted or woven, be absorbable or nonabsorbable, and offer a low-cost alternative to biologic matrices while also allowing for more control over the flexibility and tensile strength of the material.…”
mentioning
confidence: 99%
“…Biologic mesh, or acellular dermal matrix (ADM), is composed of animal or human tissue that has been stripped of its antigenic cells and processed into a matrix of collagen and elastin 10,14 . The most popular biologic mesh substrates include human, bovine, or porcine tissues, where various processing techniques preserve different cellular and extracellular materials to encourage host cell integration 15 . Synthetic meshes are generally made of manufactured polymers, such as polypropylene, polyester, or expanded polytetrafluorethylene, which may be combined with other materials to make composite matrices with varied physical properties 14 .…”
mentioning
confidence: 99%